Contribuições epistemológicas da abordagem multirreferencial para a compreensão dos fenômenos educacionais - João Martins Batista (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2004)
Presents the contributions of the multireferential approach to the understanding of educational phenomena emphasising the epistemological aspects. To this end, we discuss the historical moment in which the notion of multi-referentiality is structured as well as some of the concepts used to re-situate the epistemological questions inherent to the knowledge building process on social phenomena and, more specifically, those related to education.